Über das Verschwinden der Singularitäten - Chavinson, S. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: С. Я. Хавинсон. О стирании особенностей S. Chavinsonas. Pavienumų išnykimo klausimu